Photochemical R2PI study of chirality and intermolecular forces in supersonic beam - A. Giardini Guidoni; S. Piccirillo; D. Scuderi; M. Satta; T. M. Di Palma; M. Speranza; A. Filippi; A. Paladini (International Journal of Photoenergy)
One and two-color, mass selected R2PI spectra of the S1←S0 transitions in the bare (+)-(R)- 1-phenyl-1-ethanol (ER) and its complexes with different solvent molecules (solv) (-)-(R)-2-butanol (BR) or (+)-(S)-2-butanol (BS), (—)-(R)-2-pentanol (TR) or (+)-(S)-2-pentanol ( TS) and (-)-(R)-2-butylamine (AR) or (+)-(S)-2-butylamine (AS), have been recorded after a supersonic molecular beam expansion. The one-color R2PI excitation spectra of the diastereomeric complexes are characterized by significant shifts of their band origin relative to that of bare ER. The extent and the direction of these spectral shifts are found to depend upon the structure and the configuration of solv and are attributed to different short-range interactions in the ground and excited states of the complexes. In analogy with other diastereomeric complexes, the phenomenological binding energy of the homochiral cluster is found to be greater than that of the heterochiral one. Preliminary measurements of excitation spectrum of (+)-(R)-1-Indanol (IR) is also reported.